2009
DOI: 10.1177/104063870902100501
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Natural Highly Pathogenic Avian Influenza H5N1 Infection in Wild Tufted Ducks (Aythya Fuligula)

Abstract: Abstract. Highly pathogenic avian influenza (HPAI) subtype H5N1 is an infectious systemic viral disease that results in high morbidity and mortality in poultry, and has been reported in a wide range of wild bird species during the last few years. An outbreak of HPAI H5N1 occurred in wild birds in Sweden in 2006 that affected several duck species, geese, swans, gulls, and raptors. Tufted ducks (Aythya fuligula) accounted for the largest number of positive cases and, therefore, were selected for more in-depth hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 29 publications
(99 reference statements)
9
37
1
1
Order By: Relevance
“…In agreement with the report of Brojer et al (2009), we found that RT-PCR is more sensitive to the detection of AI H5N1 in biological samples and tissues (data not shown). Phylogenetic analysis of the HA and NA gene sequences showed the affiliation of the isolated AI H5N1 virus to clade 2.2.1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with the report of Brojer et al (2009), we found that RT-PCR is more sensitive to the detection of AI H5N1 in biological samples and tissues (data not shown). Phylogenetic analysis of the HA and NA gene sequences showed the affiliation of the isolated AI H5N1 virus to clade 2.2.1.…”
Section: Discussionsupporting
confidence: 92%
“…Although other organs such as the spleen, the proventriculus, the intestine, and the bursa of Fabricius showed lesions of discoloration, atrophy, necrosis and petechial hemorrhage (data not shown), we are not in favor of attributing them to the AI infection, since no viral antigens were detected in these organs. In previous studies that investigated the pathology of AI viruses during natural infection, a dichotomy of the virus antigen localization and tissue injury was frequently reported (Brojer et al 2009, van Riel et al 2009). The authors attributed this dichotomy to the inadequacy of virus antigens for immunohistochemical staining in necrosed tissue or to the effect of another pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, Bröjer and colleagues (2009) reported few only gross lesions in tufted ducks naturally infected with H5N1 in Sweden in which lung congestion, red-brown mottling of the pancreas and moderately enlarged spleens have been observed. The exhibited differences in gross lesions between our findings and those by Teifke (2007) and Bröjer (2009) may be due to the different susceptibility of different bird species that have been evaluated. In naturally infected freeliving birds, the clinical and pathologic picture of viral infection is influenced by several factors, such as the age of the bird, the amount and routes of viral exposure, the presence of concomitant infections, the levels of immunity acquired during previous exposure to influenza viruses, and the time course of the infection (Kalthoff et al, 2008).…”
Section: Discussioncontrasting
confidence: 50%
“…29 In addition, whooper swans and mute swans may have hemorrhages in multiple organs, in accordance with the endotheliotropism of HPAIV H5N1 in these species. [52][53][54] Virus shedding occurs mostly from the pharynx and lasts from 3 to 11 d in wild waterbirds following experimental infection. 29 Although HPAIV H5N1 have caused self-limiting epidemics in wild waterbirds, it remains unknown whether they can be maintained in wild waterbird populations.…”
Section: Pathology and Host Responsesmentioning
confidence: 99%
“…It rarely occurs in wild birds infected with HPAIV H5N1, but was reported in mute swans (Cygnus olor), whooper swans (C. cygnus) and tufted ducks (Aythya fuligula). [52][53][54] Infection of parenchymal cells, mainly in the pancreas, brain, heart, kidney and skeletal muscle, may occur, essentially in poultry surviving the acute phase of infection. 29 In humans, LPAIV and HPAIV preferentially infect respiratory epithelial cells, in particular along the deeper regions of the respiratory tract.…”
Section: Do Not Distributementioning
confidence: 99%